1971
DOI: 10.1136/thx.26.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Peak flow rate in Nigeria: Anthropometric determinants and usefulness in assessment of ventilatory function

Abstract: The inexpensive nature of the peak flow rate (PFR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

1972
1972
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 14 publications
5
17
0
Order By: Relevance
“…The results were consistent with those of another study which was conducted [6]. with those of the studies which were conducted by researchers [7]. On comparison, according to three height sub-groups, mean PEFR of study subjects was found to be less than that of control subjects and this result was statistically highly significant.…”
Section: Discussionsupporting
confidence: 82%
“…The results were consistent with those of another study which was conducted [6]. with those of the studies which were conducted by researchers [7]. On comparison, according to three height sub-groups, mean PEFR of study subjects was found to be less than that of control subjects and this result was statistically highly significant.…”
Section: Discussionsupporting
confidence: 82%
“…This study also showed that in males, PEFR increases significantly with height (r=0.294) and weight (r=0.845), which is in agreement with the reports of certain other investigators. [30,31,32,33] A large sample by increasing size and random selection of subjects from general population instead of students of medical school is needed to get more accurate results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently various scientific studies have been carried out to relate PEFR to height and weight of the subjects. [10,11,12,13] Conflicting reports have also been documented [14]. The present study has been taken up to look into the relationship between PEFR and anthropometric parameters such as height and weight in males and females and determining which factor has a stronger association with PEFR.…”
Section: Introductionmentioning
confidence: 99%
“…The recordings were done between 12hr and 17hr after the worker had been exposed to wood dust during the day's work. the predicted PEFR for each subject using the formula; y = c+ b 1 X 1 + b 2 X 2 where y = predicted PEFR, c = constant, b 1 X 1 = product of age (yrs) and coefficient of age and b 2 X 2 = product of height (cm) and coefficient of height (Elebute & Femi-Pearse, 1971). The ratio of observed PEFR and predicted PEFR (%) was calculated for each subject.…”
Section: Sampling Methodsmentioning
confidence: 99%